Omega-3 Supplementation for Cognition and Focus in Petanque Athletes: A Literature Review - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This literature review examines the effects of omega-3 supplementation, specifically EPA and DHA, on cognitive performance and focus among athletes, with a particular emphasis on precision sports such as petanque. A total of 18 eligible studies published between 2015 and 2025 were systematically analyzed using the PRISMA guidelines. The databases Scopus, PubMed, Web of Science, DOAJ, Google Scholar, and national Indonesian portals were searched. The findings indicate that omega-3 supplementation consistently improves cognitive outcomes—including selective attention, sustained focus, working memory, reaction time, and executive function. DHA was shown to enhance membrane fluidity, synaptic transmission efficiency, and neuroplasticity, while EPA contributed to reducing neural inflammation and cognitive fatigue. These mechanisms explain improvements observed in athletes requiring high mental precision. Despite the positive findings, several limitations remain, including heterogeneity in dosage, supplementation duration, cognitive measurement tools, and the lack of specific research on petanque athletes. Future research should include randomized controlled trials focusing directly on petanque populations and explore neurocognitive measures such as EEG or neuroimaging. Overall, omega-3 represents a promising nutritional strategy for improving cognitive readiness, focus, and performance in precision-based sports.